Distinctive pitted enamel hypoplasia and short stature - Koch, Martin Jean; Spranger, Stephanie; Bettendorf, Markus (Journal of craniofacial genetics and developmental biology, 2000)
We report a case of postnatal onset short stature and a distinctive pitted enamel hypoplasia in a 19-year-old woman. Growth hormone deficiency and other endocrine deficiencies were excluded. Additional observations of similar cases might outline a newly recognized syndrome.